Kemampuan Literasi Media Mahasiswa Ilmu Perpustakaan dalam Menanggulangi Berita Hoaks di Media Sosial - Lubis, Rizkiyatun Fadillah (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
This study aims to determine the ability of Library Science students to analyzehoax news on social media, the ability of Library Science students to access hoaxnews on social media, the relationship between the media literacy skills of LibraryScience students in tackling hoax news on social media, and the ability of LibraryScience students to evaluate news. hoaxes on social media.This study uses quantitative research using a questionnaire as a means ofcollecting data obtained from respondents. The population of this study were allLibrary Science students of UIN North Sumatra from the 2019 stambuk, 2020 and2021, namely 352 students with a total sample of 79 students determined by theslovin formula. The sampling technique used to determine the sample is RandomSampling/Probability Sampling. To measure the relationship between the medialiteracy abilities of Library Science students at UIN North Sumatra in tacklinghoax news on social media and test hypotheses using the Spearman's Rho RankOrderCorrelations formula and Guilford's calculations. The results showed that media literacy ability had a positive relationship with a value of 0.358 which indicated a strong enough relationship in tackling hoax news.